Tracking lithium penetration in solid electrolytes in 3D by in-situ synchrotron X-ray computed tomography. (April 2021) - Hao, Shuai; Daemi, Sohrab R.; Heenan, Thomas M.M.; Du, Wenjia; Tan, Chun; Storm, Malte; Rau, Christoph; Brett, Dan J.L.; Shearing, Paul R.
Abstract: Solid state batteries have attracted extensive attention, but the lithium penetration through the solid electrolyte remains a critical barrier to commercialisation and is not yet fully understood. In this study, the 3D morphological evolution of cracks with deposited lithium were tracked as they penetrated through the solid electrolyte during repetitive plating. This is achieved by utilising in-situ synchrotron X-ray computed tomography with high spatial and temporal resolutions. Thin-sheet cracks were observed to penetrate the solid electrolyte without immediate short-circuiting of the cell. Changes in their width and volume were quantified. By calculating the volume of deposited lithium, it was found that the lithium was only partially filled in cracks, and its filling ratio quickly dropped from 94.95% after the 1st plating to ca. 20% after the 4th plating. The filling process was revealed through tracking the line profile of grayscale along cracks. It was found that lithium grew much more slowly than cracks, so that the cracks near the cathode side were largely hollow and the cell could continue to operate. The deposited lithium after short circuit was segmented and its distribution was visualised. DVC analysis was applied to map local high stress and strain, which aggregated along cracks and significantly increased at areas where new cracks formed. Graphical Abstract: ga1 Highlights: The 3D morphological evolution of cracks and deposited Li was tracked by in-situ X-ray CT during plating until short circuit. Lithium only partially filled the cracks, and propagated more slowly than the cracks resulting in a lag of short circuit. The lithium filling ratio dropped from 94% to ca. 20% during plating, primarily due to the high speed of crack growth. Stress and strain in the LPS aggregated along the cracks and their branches, forcing cracks to propagate in these areas.